Application of upper-limb dynamic pseudoelastic splinting in the treatment of stroke chronic patient: a pilot assessment. (17th February 2021) - Garavaglia, Lorenzo; Gasperini, Giulio; Lazzari, Fabio; Molteni, Franco; Pittaccio, Simone
Abstract: Purpose: The chronic sequelae of stroke are often a strong limitation to patient's quality of life. New non-invasive elective treatments are required to support postural and functional improvements long after the primary insult. This study is an uncontrolled pilot evaluation of pseudoelastic orthotics for post-stroke upper-limb rehabilitation. Materials and methods: Six chronic hemiplegic patients (3.8 ± 1.7 years since stroke) were evaluated with clinical scales, covering the ICF domains of body functions and structures (Modified Ashworth Score [MAS], Medical Research Council Scale for Muscle Strength, Fugl-Meyer [FM], Motricity Index [MI]), activities (Wolf Motor Function Test [WMF], Motor Activity Log [MAL]) and participation (quality of life questionnaires); sensors applied to the orthosis were used to assess changes in the articular and functional domains over a month's treatment. Results: Significant gains were achieved in elbow spasticity (MAS, p  = .020), upper-limb motor function (FM, p  = .005), reaching task ( p  = .035), and gait ( p  = .00046) speed. Most patients improved in functional tasks (WMF), but this did not reflect in daily-life activities as measured with MAL. Some patients reported an improved quality of life, especially the quality of sleep. Conclusions: Pseudoelastic orthoses could be a comfortable and useful adjunct in the long-term management of stroke. Broader trials will have to confirm these preliminary observations. Implications for rehabilitation: Use of new materials in neuromuscular rehabilitation. Customised and adjustable therapeutic action obtained with dynamic personalised orthoses. Non-invasive interventions could be of help for patients with chronic disability.